Critical incidents in the development of (multi)ethnic-racial identity: Experiences of individuals with mixed ethnic-racial backgrounds in the U.S. (May 2020) - Cardwell, Megan E.; Soliz, Jordan; Crockett, Lisa J.; Bergquist, Gretchen L.
Secure ethnic-racial identity (ERI) is tied to well-being, especially for minority individuals; however, there is still little consensus on the key processes and optimal outcomes of various multiethnic-racial (ME-R; i.e., individuals with parents from different ethnic-racial groups) identity development models. In this study, we examine the critical incidents in personal and social relationships that are central to ME-R identity development. Twenty-nine ME-R individuals provided retrospective accounts of incidents and conversations they self-perceived to be critical to their ERI development. Four major themes emerged: incidents and conversations surrounding intergroup contact, confrontation, heritage, and appearance were all recalled as critical to ME-R identity development. These findings highlight the importance of studying the ways that ERI is constituted through interaction with others. Implications and directions for future research are discussed.